Plagiarism Trademark Dispute between Ms Glow and Ps Glow: Case Study Judge's Decision No. 2/Pdt.Sus-HKI/Merek/2022/PN Niaga Mdn - Junaidi; Hodriani; Perangin-angin, Reh Bungana Beru (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
In the realm of business and competitive markets, branding plays a crucial role. A brand serves as a key identifier with the primary goal of distinguishing an entrepreneur's products from those of competitors. This article examines the trademark dispute between MS Glow and PS Glow, revealing two different rulings from the same legal case, specifically the cancellation of a trademark. The differing interpretations of the Trademark and Geographical Indications Law by the judges have raised concerns, prompting scrutiny of the clarity in the application of trademark law in Indonesia. This research uses a normative method, utilizing secondary data that includes primary legal materials such as court decisions and legislative texts related to trademarks. Additionally, secondary legal materials such as journals and books are referenced to enhance understanding. The data analysis methodology employed is qualitative juridical analysis. The findings show that both cases share a common issue similarity in beauty product brands. Each party claims to possess legitimate intellectual property rights and asserts that they have avoided any trademark infringement. Notably, the legal dispute between PS Glow and MS Glow does not fall under the Nobis in Idem principle, as the lawsuit filed in the Surabaya court was initiated before the Medan Commercial Court’s decision had been finalized. This study offers important insights into trademark disputes, the application of trademark law in Indonesia, and the complexities involved in handling trademark conflicts between competing parties.